Update: Causes and symptoms of sudden cardiac death in young athletes - Asif, I. M.; Yim, E. S.; Hoffman, J. M.; Froelicher, V. (The Physician and Sportsmedicine, 2015)
Sudden cardiac death (SCD) is the leading cause of death during exercise. While initial reports suggested that the most common cause of SCD in young athletes was due to hypertrophic cardiomyopathy (HCM), a critical review of investigations in several populations (athletes, non-athletes, military, national, and international) supports that the most common finding at autopsy of young individuals with SCD is actually a structurally normal heart (SNH). This information is vital for sports medicine clinicians, especially with regard to the pre-participation evaluation (PPE) since cardiac death associated with a SNH is likely attributed to disorders such as arrhythmia or ion channel diseases. This comprehensive review explores the causes of SCD, along with the symptoms preceding death, which ultimately may help refine the PPE and maximize the ability to detect potentially lethal disease prior to competition.